Transition of TiO2 nanotubes to nanopores for electrolytes with very low water contents - Wei, Wei; Hauser, Christina; Wei, Wei; Berger, Steffen; Hauser, Christina; Meyer, Karsten; Yang, Mingjun; Schmuki, Patrik (Electrochemistry Communications, 2010)
Over the past decade, the electrochemical formation of self-organized nanotube layers in dilute fluoride containing electrolytes has been studied intensively. In the present work, we show that by anodization of Ti in similar electrolytes but containing only very low water contents, the formation of ordered TiO nanoporous structures can be observed. I.e., the water content in the electrolyte is the critical factor that decides whether self-ordered oxide tubes or pores are formed. This supports the concept that tube formation originates from ordered porous oxide by a "pore-wall- splitting" mechanism. © 2010 Elsevier B.V. All rights reserved.